Application of Digital Storytelling (DST) Elements to Enhance the Educational Potential of Museum Exhibitions: Insights from Literature Reviews and Content Analysis - Hafizah ROSLI; Norfadilah KAMARUDDIN; Badrul ISA (Communications of International Proceedings, 2024)
Digital storytelling (DST) holds significant educational promise, fostering self-reflection and immersing individuals in their personal and cultural narratives. DST is becoming a common trend in culture and heritage research internationally. However, most studies in the field of DST have only focused on education enhancement, specifically in Malaysia.  The study aimed to identify essential elements of DST suitable for use in cultural and heritage contexts, specifically in museum exhibitions. Through qualitative methodology, specifically content analysis, contributions from experts and international scholars were analysed to compile these elements. As a result, ten essential elements were identified from a diverse range of experts and scholars, creating a comprehensive guide for digital story development in museum exhibitions. The findings suggest that reshaping DST elements based on expert feedback is beneficial, as experts provided unique definitions highlighting their importance for settings like museum exhibitions. This valuable information can contribute to developing comprehensive DST guidelines for curators and enhance our understanding of common DST elements. It's important to note that while this information may have limitations about non-interactive elements, it establishes the foundation. for future research to explore DST elements across different fields.
Keywords: Content Analysis; Culture Heritage; Digital Storytelling Museum Exhibition